Decision-making process during the fulfilment of military assignments - Mitacek, Radek; Zeman, Tomas; Drozd, Jan; Ondrousek, Lubos; Ullrich, David; Dvorak, Jiri (Vojnotehnički glasnik / Military Technical Courier, 2017)
The paper deals with the decision-making process in crisis management with focus on the Army of the Czech Republic (soldiers at the University of Defence in Brno). Within the research, 44 soldiers were monitored whilst managing various tactical situations during a three-week complex field training exercise. The soldiers were supposed to carry out the following combat assignments: fire control, battle order and radio operation. Prior the training, the soldiers filled out a questionnaire the questions in which corresponded with the above mentioned practical tasks. Based on the acquired outcomes, it may be stated that the assessment of theoretical solution of selected combat assignments among future squad leaders may be used for the prediction of how successful the management of such assignments may be in practice.